Mental health of Urban Mothers (MUM) study: a multicentre randomised controlled trial, study protocol - Ewa Andersson; Liping Zhu; Ganesh Acharya; Simone Eliane Schwank; Ho-Fung Chung; Mandy Hsu; Shih-Chien Fu; Li Du; Hsuan-Ying Huang (BMJ Open)
Introduction Mental health disorders are common during pregnancy and the postnatal period and can have serious adverse effects on women and their children. The consequences for global mental health due to COVID-19 are likely to be significant and may have a long-term impact on the global burden of disease. Besides physical vulnerability, pregnant women are at increased risk of mental health problems such as anxiety, depression and post-traumatic stress disorder due to the consequences of social distancing. It can result in altered healthcare routines, less support from the family and friends, and in some cases, partners not being allowed to be present during prenatal visits, labour and delivery. Higher than expected, rates of perinatal anxiety and depression have been already reported during the pandemic. Pregnant women may also feel insecure and worried about the effects of COVID-19 on their unborn child if they get infected during pregnancy. Today, young urban women are used to using internet services frequently and efficiently. Therefore, providing mental health support to pregnant women via internet may be effective in ameliorating their anxiety/depression, reducing the risk of serious mental health disorders, and lead to improved maternal and perinatal outcomes.Overarching aim Our aim is to explore the effectiveness of a web-based psychosocial peer-to-peer support intervention in reducing the risk and severity of perinatal mental health disorders and preventing adverse pregnancy outcomes among pregnant women living in metropolitan urban settings.Methods and analysis We plan to conduct a multicentre prospective randomised controlled trial, Mental health of Urban Mothers trial. Pregnant women living in large metropolitan cities will be recruited using internet-based application through non-profit organisations’ websites. The women who consent will be randomised to receive a web-based peer-to-peer support intervention or usual care. Data will be analysed to identify the effects of intervention on Edinburgh Postnatal Depression Score and Generalised Anxiety Disorder 7 scores as well as pregnancy outcomes. The impact of COVID-19 pandemic on maternal stress will be assesed using Impact Event Scale-R. Any differences in outcomes between cities will be addressed in subgroup analyses.Ethics and dissemination The study will be conducted according to the principles of Good Clinical Practice and will follow the ethical principles of the Declaration of Helsinki. The study protocol has been approved by the ethical review board of Chinese University of Hong Kong (IRB number 2019-8170) and Shanghai Center for Women’s and Children’s Health (international review board (IRB) number 2020-F001-12). The results will be disseminated at national and international scientific conferences, published in peer-reviewed medical journals and spread to the public through social media, news outlets and podcasts.Trial registration number NCT04363177; Trial sponsor Karolinska Institute, CLINTEC, Stockholm, Sweden.